Manajemen Kelas dalam Meningkatkan Motivasi Belajar Siswa di SDN Kalitapen 1 Bondowoso - Zulfa Lailatus Syarifah (Idarotuna: Jurnal Manajemen Pendidikan Islam, 2024)
Effective classroom management is a key factor in enhancing student motivation. This research aims to analyze the classroom management strategies implemented by teachers at SDN Kalitapen 1 Bondowoso and their impact on student motivation. A qualitative approach was employed with data collection methods including observation, in-depth interviews, and documentation. Data were analyzed using Miles and Huberman's interactive model, with source triangulation ensuring data validity. The results indicate that classroom management strategies involving time management, seating arrangements, technology use, rewards, and challenges tailored to students' abilities significantly increased student engagement and motivation. In conclusion, good classroom management plays a crucial role in creating an effective and inclusive learning environment.